The sun does shine [compact disc, unabridged] : how I found life and freedom on death row - Hinton, Anthony Ray; Hardin, Lara Love (Macmillan Audio, 2018)
A man who spent thirty years on death row for a crime he did not commit describes how he became a victim of a flawed legal system, recounting the years he shared with fellow inmates who were eventually executed before his exoneration.